The First Experience of Laparoscopic Gastroepiploic Artery Harvesting during Complete Autoarterial Myocardial Revascularization - A. Gabriyelyan; A. Sidyuk; A. Mazur; T. Domanskyy; O. Beregovoy; V. Beleiovych; A. Mironyuk; S. Romanova; I. Kudlai; I. Havin; G. Savenko (Український журнал серцево-судинної хірургії, 2019)
The use of autoarterial grafts for myocardial revascularization is a priority for cardiac surgery. Laparoscopic right gastroepiploic artery (RGEA) harvesting may significantly reduce the risks of complications associated with laparotomy and expand the possibilities of its use as an autoarterial graft during coronary artery bypass grafting.